Genomic Analysis of Mitochondrial Carrier Genes in the Bombyx mori - Jun CAO; Feng SHI (Journal of Integrative Agriculture, 2012)
This study is performed to investigate the mitochondrial carrier gene family in silkworm genome. In total, 30 genes are identified and claded into eight well-conserved groups. Gene duplication contributes to the expansion and complexity of this family. Diverse expression patterns suggest their functional differentiation. Analyses of the sitespecific profiles reveal critical amino acid residues for functional divergence. This study highlights the molecular evolution of the mitochondrial carrier gene family in silkworm and may provide a starting point for further experimental verification.